Estimasi Penilaian Build Operate and Transfer Atas Aset Daerah Pemerintah Kota Semarang yang Berpotensi Sebagai Wahana Wisata Alam Guna Peningkatan Pendapatan Asli Daerah - Paranita, Ekayana Sangkasari (Jurnal Ilmiah Aset, 2008)
The purpose of this research is to estimate the value of build operate and transfer (BOT) of regional asset of Semarang municipal government which has potential as natural tourism resort. All this time, a number of assets of Semarang municipality haven’t been managed optimally. At the beginning of 2008, Semarang municaplity through its legal website offered its assets to the investors to be organized cooperately. It pursued to the investors and could be contributed in enchancing regional income. The research estimates the value of BOT of asset of Semarang municipal government which has potency as natural tourism resort based on evaluation approaches that meet Indonesian Evaluation Standard of 2007. By the scenario of BOT cooperation, asset of land in Sodong is expected to be optimally managed, give contribution to regional income, and at the of BOT period, Semarang municipalty could have natural tourism resort as it profitable asset.